Studying Different Tasks of Implicit Learning across Multiple Test Sessions Conducted on the Web - Sævland, Werner; Norman, Elisabeth (Frontiers in Psychology, 2016)
Implicit learning is usually studied through individual performance on a single task, with the most common tasks being Serial Reaction Time task (SRT; Nissen and Bullemer, 1987), Dynamic System Control task (DSC; (Berry and Broadbent, 1984)) and artificial Grammar Learning task (AGL; (Reber, 1967)). Few attempts have been made to compare performance across different implicit learning tasks within the same experiment. The current experiment was designed study the relationship between performance on the DSC Sugar factory task (Berry and Broadbent, 1984) and the Alternating Serial Reaction Time task (ASRT; (Howard and Howard, 1997)). We also addressed another limitation to traditional implicit learning experiments, namely that implicit learning is usually studied in laboratory settings over a restricted time span lasting for less than an hour (Berry and Broadbent, 1984; Nissen and Bullemer, 1987; Reber, 1967). In everyday situations, implicit learning is assumed to involve a gradual accumulation of knowledge across several learning episodes over a larger time span (Norman and Price, 2012). One way to increase the ecological validity of implicit learning experiments could be to present the learning material repeatedly across shorter experimental sessions (Howard and Howard, 1997; Cleeremans and McClelland, 1991). This can most easily be done by using a web-based setup that participants can access from home. We therefore created an online web-based system for measuring implicit learning that could be administered in either single or multiple sessions. Participants (n = 66) were assigned to either a single-session or a multi-session condition. Learning and the degree of conscious awareness of the learned regularities was compared across condition (single vs. multiple sessions) and tasks (DSC vs. ASRT). Results showed that learning on the two tasks was not related. However, participants in the multiple sessions condition did show greater improvements in reaction time on the ASRT task.